Evaluasi Kinerja Karyawan dalam Suatu Perusahaan: Sebuah Kajian Kepustakaan - Ilham Saputra; Hayatul Khairul Rahmat (Journal of Current Research in Management, Policy, and Social Studies, 2024)
This study aims to determine: the definition of performance evaluation, employee performance, factors that affect employee performance, the purpose of employee performance evaluation, and the benefits of employee performance evaluation. This research uses the literature study method. The findings of this study are that performance evaluation has forms such as aiming to measure, assess, and improve employee performance. In addition, the purpose of performance evaluation is to ensure the achievement of company goals and objectives, as well as to understand the company's position and the level of achievement of company goals. In this process, performance evaluation helps in detecting delays or deviations that occur, so that they can be corrected immediately and goals or objectives are achieved.